Spatial–Temporal Dynamics and Drivers of Crop Water Footprint in Xinjiang, China - Xiaoyu Zhang; Zhenhua Wang; Jian Liu; Wenhao Li; Haixia Lin; Tehseen Javed; Xuehui Gao; Guopeng Qin; Huadong Liu; Hengzhi Wang; Yifan Liu; Hanchun Ye (Agronomy)
Efficient allocation and utilization of water resources are critical for the sustainable development of agriculture in arid regions, particularly those heavily reliant on irrigation. Xinjiang, one of China’s major agricultural regions, faces significant challenges in managing water resources due to its arid climate and dependence on irrigation. This study investigates the spatial–temporal dynamics of crop water footprint (CWF) and its driving factors in Xinjiang. Unlike previous studies on Xinjiang that primarily focus on total water footprint, this research emphasizes the crop blue water footprint (CWFB) to provide a more precise assessment of agricultural water allocation and consumption. Using the CROPWAT 8.0 model, the CWF of 14 prefectures in Xinjiang were analyzed for the period 2000–2020. Focusing primarily on the crop blue water footprint (CWFB), the study employed the Logarithmic Mean Divisia Index (LMDI) model to identify key drivers and their mechanisms. Results reveal that Xinjiang’s average annual CWF is 179.02 Gm3, with CWFB contributing 90.22% and the crop green water footprint (CWFG) accounting for. 10.05%. The CWFB showed an initial increase followed by stabilization, with Southern Xinjiang being the largest contributor, trailed by Northern and Eastern Xinjiang. Among the 14 prefectures, the top seven accounted for 90.46% of CWFB. Cotton, wheat, and maize were the major crops, comprising 47.80%, 23.14%, and 21.45% of the total blue water footprint, respectively. This study identifies the dominant role of economic effect and water use efficiency effect in driving changes in CWFB through its analysis of the driving factors. Understanding the spatial–temporal changes and key drivers of blue water consumption helps regions adjust cropping structures and agricultural water resource allocation patterns to ensure sustainable agricultural development. The findings not only offer valuable implications for policymakers and stakeholders in Xinjiang but also provide references for other arid and semiarid regions facing similar challenges in agricultural water resource management.